Programming as a need for integration in the curriculum of the subject of technology with ICT in the lower secondary schools of Kosovo - Senad Orhani (Institute of Computer Science (IOCS), 2023)
Kosovo as a small country but with bright education integrates the newest European curricula, especially in the curricular field Life and work in the subject of technology with ICT. In this scientific paper, we will discuss the need to integrate programming in the curriculum of the subject of Technology with ICT in the lower secondary schools of Kosovo. Programming is a rapidly growing field and is increasingly used in the modern world of technology. If our students will have good knowledge of programming, they will have a great advantage in their future careers. We can conclude that a long-term and clear strategy should be developed for the integration of programming in the curriculum of the subject of Technology with ICT in the lower secondary schools of Kosovo, which will help prepare students for the labor market in the field of technology and programming. Our recommendations, we suggest improving the curriculum of the ICT subject, including a project-oriented approach to help students develop practical skills in the field of programming. We also suggest more complex training for teachers to ensure they have the skills and knowledge to teach this subject in a way that is appropriate for students.